Performance of Non-Uniform Duty-Cycled ContikiMAC in Wireless Sensor Networks - Nur Rabiul Liyana Mohamed; Ansar Jamil; Lukman Hanif Audah Audah; Jiwa Abdullah; Rozlan Alias (Institute of Advanced Engineering and Science, 2017)
Wireless Sensor Network (WSN) is a promising technology in Internet of Things (IoTs) because it can be implemented in many applications. However, a main drawback of WSN is it has limited energy because each sensor node is powered using batteries. Therefore, duty-cycle mechanisms are introduced to reduce power consumption of the sensor nodes by ensuring the sensor nodes in the sleep mode almost of the time in order to prolong the network lifetime. One of the de-facto standard of duty-cycle mechanism in WSN is ContikiMAC, which is the default duty-cycle mechanism in Contiki OS. ContikiMAC ensures nodes can participate in network communication yet keep it in sleep mode for roughly 99% of the time. However, it is found that the ContikiMAC does not perform well in dynamic network conditions. In a bursty network, ContikiMAC provides a poor performance in term of packet delivery ratio, which is caused by congestion. One possible solution is ContikiMAC should increase its duty-cycle rate in order to support the bursty traffic. This solution creates a non-uniform duty-cycle rates among the sensor nodes in the network. This work aims to investigate the effect of non-uniform duty-cycle rates on the performance on ContikiMAC. Cooja simulator is selected as the simulation tool. Three different simulation scenarios are considered depending on the Clear Channel Assessment Rate (CCR) configurations: a low uniform CCR value (Low-CCR), a high uniform CCR value (High-CCR) and non-uniform CCR values (Non-uniform-CCR). The simulation results show that the Low-CCR scenario provides the worst performance of PDR. On the other hand, the High-CCR scenario provides the best performance of PDR. The Non-uniform-CCR provides PDR in between of Low-CCR and High-CCR.